(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study analyzes the Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS) in Andhra Pradesh from 2014-15 to 2021-22. It assesses trends in registered workers, job card issuances, active participation, and employment outcomes, while also examining 100-day employment achievements. Findings indicate stable participation rates and fluctuations in employment, with recommendations including awareness campaigns, simplified procedures, and targeting marginalized groups to enhance participation.